1981
DOI: 10.1139/f81-221
|View full text |Cite
|
Sign up to set email alerts
|

Native Lake Trout (Salvelinus namaycush) Stocks in the Canadian Waters of Lake Superior Prior to 1955

Abstract: Institute for Environanenlal Studies, Universiy of Toronto, Toronto, Ont. M5S dA4 GOODIER, 4. L. 1981. Native lake trout (Salvebinus namaycush) stocks in the Canadian waters of Lake Superior prior to 1955. Can. J. Fish. Aquat. Sci. 38: 1424-1734.The decline of Lake Superior lake trout (Salvelinus namaycezsh) stocks after the sea lamprey (Petromyzan marinus) population expIosion of the 1950s was both dramatic and decisive. Few native stocks remain to permit scientific data collection. However, interviews with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 7 publications
1
41
0
Order By: Relevance
“…Similarly, various lake trout forms have been reported in the Laurentian Great Lakes (Agassiz 1850; Brown et al. 1981; Goodier 1981) and more recently from large Canadian shield lakes (Blackie et al. 2003; Alfonso 2004; Zimmerman et al.…”
Section: Introductionmentioning
confidence: 72%
“…Similarly, various lake trout forms have been reported in the Laurentian Great Lakes (Agassiz 1850; Brown et al. 1981; Goodier 1981) and more recently from large Canadian shield lakes (Blackie et al. 2003; Alfonso 2004; Zimmerman et al.…”
Section: Introductionmentioning
confidence: 72%
“…Distinctive shallowwater morphs of lake charr have been described for Great Bear Lake (Blackie et al 2003;Alfonso 2004) and have been reported from the Great Lakes (Brown et al 1981;Goodier 1981;Krueger and Ihssen 1995), but enough descriptive material for across-lake comparisons is lacking. The problem is with the Laurentian Great Lakes accounts, which except for the lean morph are sparse, consisting mostly of comments on color variations and generalized descriptions of shape (e.g., racers) (Goodier 1981). Therefore, I will not discuss further the distinctive shallow-water morphs of Great Bear Lake.…”
Section: Figmentioning
confidence: 99%
“…Historical inference, based on the association of large catches of spawning condition adult lake trout with specific habitat types, was that lake trout spawned on a wide variety of substrate types, including cobble, rubble, clay, and honeycombed bedrock that were found over a wide range of depths in the Great Lakes including some rivers draining into Lake Superior (Loftus 1957;Goodier 1981;Goodyear et al 1982aGoodyear et al , 1982bGoodyear et al , 1982cGoodyear et al , 1982dThibodeau and Kelso 1990). In contrast, spawning by contemporary lake trout stocks appears restricted to cobble substrates in relatively shallow (< 15 m) water Wagner 1981;Peck 1986;Fitzsimons 1994aFitzsimons , 1995Casselman 1995;Holey et al 1995;Kelso et al 1995;Schreiner et al 1995).…”
Section: Is There a Need For Artificial Reefs In The Great Lakes?mentioning
confidence: 99%
“…Alternatively, spawning habitat site selection may have become less diverse as a result of the loss of genetic strains that spawned at greater depths or used spawning habitat other than cobble. Brown et al (1981), Goodier (1981), and Dehring et al (1981) suggested that some of the reported historic variability in spawning habitat selection was the result of multiple strains of lake trout that occurred historically in the Great Lakes. Some historic strains apparently spawned at depths > 15 m to as much as 80-90 m in Lakes Michigan and Huron and up to 180 m in Lake Superior (Thibodeau and Kelso 1990).…”
Section: Is There a Need For Artificial Reefs In The Great Lakes?mentioning
confidence: 99%